The way of the house husband. 2 - Oono, Kousuke; LeBlanc, Jennifer (Viz signature., 2020)
"The legendary yakuza 'the Immortal Dragon' has washed his hands of the gangster life for something far more dangerous--becoming a househusband! Cleaning, laundry, grocery shopping, cooking ... These days he's doing everything he can to succeed as man of the house, if it doesn't kill him first! The cozy yakuza comedy continues!"--Provided by publisher